2017
DOI: 10.1016/j.jccase.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate poisoning presenting as out-of-hospital cardiac arrest: A clinical challenge

Abstract: A B S T R A C TOut-of-hospital cardiac arrest (OHCA) remains a challenge for physicians since effective management and definitive salvage depend upon correct determination of the etiology and the extent of injury. Definitive diagnosis of organophosphate poisoning (OP) requires physicians' clinical awareness of a typical toxidrome, that is, characteristic signs and symptoms of poisoning, and laboratory confirmation.Here we report a case of an OHCA patient with OP, which was initially misdiagnosed as an acute ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The signs of OPP may be classified as effects secondary to nicotinic, muscarinic, and CNS receptor overstimulation. 6 Clinical presentation depends on the specific agent involved, the type of exposure and the quantity absorbed 5 .Miosis was also the most significant sign in the present patient (99.65%). This finding is similar to several studies.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The signs of OPP may be classified as effects secondary to nicotinic, muscarinic, and CNS receptor overstimulation. 6 Clinical presentation depends on the specific agent involved, the type of exposure and the quantity absorbed 5 .Miosis was also the most significant sign in the present patient (99.65%). This finding is similar to several studies.…”
Section: Discussionmentioning
confidence: 63%
“… 2 , 4 , 16 Pralidoxime is a biochemical antidote for OPP; its beneficial effects include reactivation of cholinesterase by cleavage of phosphorylated active sites, direct reaction and detoxification of unbounded OPCs, and an endogenous anticholinergic effect. 3 - 5 This therapy for OPP also applies to the emergency treatment for sarin, a typical drug of chemical weapons of mass destruction. 7 , 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, a nationwide population-based cohort study conducted by Hung et al, 2015 confirmed that, individuals undergone OP poisoning have greater incidence rates of congestive heart failure than a non-OP poisoning cohort. Notably, out-of-hospital cardiac arrest may also be an outcome of OP intoxication ( Kuo et al, 2017 ). Statistical analyses on a cohort of 7557 individual suggested that, occupational exposure to pesticides including OPs might play a role in the development of cardiovascular diseases including coronary heart disease ( Berg et al, 2019 ).…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…Washington, DC, US, Government Printing Office) [17]. In humans, many reports of acute poisoning of organophosphates research suggested that organophosphate acts similar to nerve agents and may cause muscle failure, resulting in a patient's death [18][19][20].…”
Section: Introductionmentioning
confidence: 99%